Epidemiologic Transition in Iran with Emphasis on the Third Stage of Transition - mohamad sasanipour; Sajjad Asadi (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: During the last half century, all indices of mortality imply the prompt and continuous decrease of nationwide mortality. Alongside reduction of mortality, there happened a comprehensive form of transition of mortality causes, from epidemical and other communicable diseases such as mothers' (birth giving) mortalities and birth related ones, to other causes like chronic diseases related to lifestyle and aging. Methods: in this study, stages of epidemiological transition in Iran with emphasis on the third transition, is surveyed and finally deals with prediction of this trend in future decades. Results: the results show that Iran has been through the third stage of epidemiological transition for two recent decades since a large proportion of deaths are related to chronic disease such as cardiovascular disease and life expectancy at birth has decreased to 70 years. There also observed signs of the fourth transition in Iran in recent years, because as deaths caused by chronic diseases have increased, the mean age of death has also increased remarkably. Conclusion: epidemiological transition dynamic and changes of death causes, must be considered according to other demographic components. Reduction of death rate, fertility related changes, and as a result changes of age structure are some causes that influence on epidemiological transition in Iran and will be influencing for some years later. Key words: epidemiological transition, life expectancy at birth, death causes, population dynamics.